2D DOA estimator for coherently distributed sources using one snapshot. Issue 19 (26th July 2019) - Lin, Qingqing; Jing, Meng; Shuai, Ping; Huang, Liangwei
Abstract : A two‐dimensional (2D) direction‐of‐arrival (DOA) estimation method for coherently distributed (CD) sources has been proposed in high real‐time situation using only one snapshot. Utilising two uniform linear arrays (ULAs), the proposed algorithm first construct four equivalent matrices with rotational structures using one snapshot, and then a total equivalent covariance is extended by the four matrices. Finally, two rotational invariance matrices can been calculated by ESPRIT‐like algorithm, and the eigenvalues which contains of the information of the central DOAs can be obtained by eigen‐decomposition of the two matrices. To improve the performance of the proposed method, in‐phased accomplished data is proposed. Without snapshots accumulation, peak searching, and correlation process, the 2D DOA estimation method for CD sources can be used for real‐time situation. Several simulation results are used to illustrate the performance of the proposed method.